Synthesis of graphene oxide and graphene quantum dots from miscanthus via ultrasound-assisted mechano-chemical cracking method - Yan, Yuxin; Manickam, Sivakumar; Lester, Edward; Wu, Tao; Pang, Cheng Heng (2021)
Whilst graphene materials have become increasingly popular in recent years, the followed synthesis strategies face sustainability, environmental and quality challenges. This study proposes an effective, sustainable and scalable ultrasound-assisted mechano-chemical cracking method to produce graphene oxide (GO). A typical energy crop, miscanthus, was used as a carbon precursor and pyrolysed at 1200 ◦C before subjecting to edgecarboxylation via ball-milling in a CO2-induced environment. The resultant functionalised biochar was ultrasonically exfoliated in N-Methyl-2-pyrrolidone (NMP) and water to form GOs. The intermediate and endproducts were characterised via X-ray diffraction (XRD), Raman, high-resolution transmission electron microscopy (HR-TEM) and atomic force microscopy (AFM) analyses. Results show that the proposed synthesis route can produce good quality and uniform GOs (8–10% monolayer), with up to 96% of GOs having three layers or lesser when NMP is used. Ultrasonication proved to be effective in propagating the self-repulsion of negativelycharged functional groups. Moreover, small amounts of graphene quantum dots were observed, illustrating the potential of producing various graphene materials via a single-step method. Whilst this study has only investigated utilising miscanthus, the current findings are promising and could expand the potential of producing good quality graphene materials from renewable sources via green synthesis routes.